Style consistency and mutual fund returns: the case of Russia - Adiya Bayarmaa; Guglielmo Maria Caporale (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper carries out style analysis for Russian mutual funds using monthly data from the National Managers' Association over the period January 2008-December 2017; specifically, it applies the RSBA method developed by Sharpe (1992) for evaluating the impact of style on returns, and uses the Style Drift Score (SDS) introduced by Idzorek (2004) as a measure of a fund's style drifting activity. The main findings can be summarised as follows. In the Russian case there is a significant positive relationship between style consistency and profitability of funds. Further, Russian funds are characterised by a high level of style drift, namely deviations from the investment strategy declared at the time of registration as required by Russian law.
Keywords: C23; G14; G19; 330; mutual funds; style consistency; performance; Russia